LEGAL OPINION: Does China Can Be Sued for The Global Pandemic? - Pulung Widhi Hari Hananto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
This legal opinion will be constructed on the current issues and chronological basis of following facts: 1. Chinese authorities have chosen denial, censorship and bluster during the early stages of the virus progression rather than the transparency that might save lives. 2 The China government blocked the COVID agenda at the United Nations Security Council (UNSC). 3. The China’s regime transmission of patently false information has made matter worse. 4. In addition, China has deliberately gives incorrect data to WHO.